COST VOLUME PROFIT ANALYSIS AS A PROFIT PLANNING INSTRUMENT - Siti Mahmudah; Dianita Meirini (State Islamic Institute (IAIN) Tulungagung, 2021)
Abstract: Profit planning is very important for the survival of the company because with profit planning, management can manage the strategies used in the company. One of the tools to do profit planning is to analyze the cost of profit volume. These three components are closely related in a company's profit planning. Cost, volume and profit analysis (Cost Volume Profit Analysis) is the main element in preparing the income statement in a company. Cost, volume and profit analysis is an examination of how total revenue and total costs change as sales volume changes. The method and type of research used is descriptive qualitative with primary data sources and secondary data, which is processed with the help of Microsoft Excel application to separate several cost data, as well as processing financial data with analysis of margin of safety, break even point, margin of safety, and analysis. profit planning. The results of this study are the MSMEs of Herbal Medicine Powder Sari Alam Trenggalek from 2018-2020 sales are always above the break even point with a high margin of safety ratio. The profit target in 2020 is not in accordance with the plan. Therefore, MSME Herbal Medicine Bubuk Sari Alam Trenggalek must increase the selling price of each product by 25% and increase sales volume by 16,439 units so that the planned profit target is achieved.